2015
DOI: 10.1007/s00158-014-1217-5
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization of a runflat structure based on multi-objective genetic algorithm

Abstract: Runflat structure plays an important role in determining the sustainable mileage after the tire is shot. Lightweight, stiffness and strength are highly relevant to the overall performance of the structure. A parameterized model was built based on the full study of the structure, and a new adaptive meshing method is proposed to ensure the quality of the model. The accuracy of the new model was verified by comparing to the traditional finite element model. The parameter study was carried out to investigate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…With the increase of the order, the ability to simulate a nonlinear model becomes stronger. Among them, the response surface model with the second-order polynomial approximation has a higher computational accuracy and problem-solving efficiency . In the current research, to fit the experimental data, the below second-order polynomial approximation was used …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increase of the order, the ability to simulate a nonlinear model becomes stronger. Among them, the response surface model with the second-order polynomial approximation has a higher computational accuracy and problem-solving efficiency . In the current research, to fit the experimental data, the below second-order polynomial approximation was used …”
Section: Methodsmentioning
confidence: 99%
“…Among them, the response surface model with the second-order polynomial approximation has a higher computational accuracy and problem-solving efficiency. 31 In the current research, to fit the experimental data, the below second-order polynomial approximation was used. where y refers to the objective function, β ij , β ii , β i , and β 0 are the polynomial coefficients, x i and x j indicate the independent variables, and k denotes the number of independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…The FE method for numerical simulation has been developed immensely over the years and is becoming an indispensable technique in vehicle engineering research. 15 In this section, the crashworthiness analysis of the commercial vehicle has been performed by using the non-linear FEA method. The full-scale FE model of the vehicle has been built to simulate the vehicle behavior under the frontal crash, which has been validated through a real crash test.…”
Section: Crashworthiness Analysis Of a Commercial Vehiclementioning
confidence: 99%
“…Kumar’s research also extracted the force and moment (F&M) characteristics and compared them with those of a passenger car tire (Kumar and Kumar, 2016). A multi-objective optimization model of a non-inflatable, explosion-proof wheel was established using the optimal Latin design method and a response surface model developed by Zhou G. et al Moreover, the wheel’s structure was optimized through the NSGA-II multi-objective genetic algorithm (Zhou et al , 2015). Based on the static behavior of three types of non-pneumatic tires with the same honeycomb cell wall thickness, the static bearing capacity of honeycomb tires was further studied by Jin, X. et al The results showed that the maximum stresses in a non-pneumatic tire’s spokes and tread were considerably lower than for traditional pneumatic tires with a higher loading capacity (Jin et al , 2018).…”
Section: Introductionmentioning
confidence: 99%